Tingkat Populasi dan Waktu Infestasi Hama Penggulung Daun (Lamprosema indicate F.): Pengaruhnya Terhadap Hasil Kacang Tanah - Jauharlina Jauharlina (Jurnal Agrista, 2006)
Population Rate and Infestation Time of Leaves Rollers Insect (Lamprosema indicate F.): The Effect of Peanut YieldABSTRACT. Study of population rate and infestation time of larvae of L. indicate on peanut yield was conducted in Experimental Farm of Agriculture Faculty, Syiah Kuala University, Darussalam, Banda Aceh. Factorial completely randomized design was applied. The first factor was population rate of L. indicata, consisting of four levels i.e. 0, 1, 3, and 6 larvae per plant. The second factor was infestation time of L. indicata larvae, consisting of four levels i.e. at time of 14, 21, 28, 35 day after planting. Each treatment was repeated three times. Variable observed were infestation intensity of L. indicata, the number of pods, the number of grain per plant, and dried grain weight per plant. The result showed that there was significant interaction between population rate and infestation time on infestation intensity of L. indicata. Population rate of 1 larvae per plant and infestation time of 35 day after planting was effective to lessen infestation intensity up to 4,88 percents. Population rate of 1 larvae per plant caused the highest number of pod, grain, and dried grain weight per plant compared to those of the population rate of 3 and 6 larvae per plant. On the contratry, the infestation time of 14 days after planting caused the lowest number of pod, grain, and dried grain weight per plant compared to that infestation time 35 day after planting.